2017
DOI: 10.1093/jjco/hyx110
|View full text |Cite
|
Sign up to set email alerts
|

The impact of young age on the prognosis for colorectal cancer: a population-based study in Taiwan

Abstract: Background: The impact of age as a prognostic factor for patients with colorectal cancer (CRC) remains controversial, possibly due to heterogeneity between studies in terms of patient numbers, percentage of patients undergoing curative resection, percentage of patients receiving neoadjuvant therapy, or failure to adjust for potential confounding factors. This study used colorectal cancer survival data from the Taiwan Cancer Registry database in order to comprehensively analyze age as a prognostic factor. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 35 publications
1
29
1
1
Order By: Relevance
“…There are several studies showing that younger patients are living longer than older patients, 37 whereas others are showing opposite results. 38 In our study, age at diagnosis failed to show significance regarding OS ( P = .331).…”
Section: Discussioncontrasting
confidence: 56%
“…There are several studies showing that younger patients are living longer than older patients, 37 whereas others are showing opposite results. 38 In our study, age at diagnosis failed to show significance regarding OS ( P = .331).…”
Section: Discussioncontrasting
confidence: 56%
“…Wang et al 37 studied 509,934 CRC patients from 3 databases (West China, SEER, and Linkoping Cancer) and reported that younger individuals (aged 50) had better survival despite having advanced disease compared to older individuals (aged > 50). However, in contrast, Chou et al 38 studied 62,060 CRC cases from a Taiwanese population and reported that individuals aged 40 had poor overall survival compared to those aged 41 to 70.…”
Section: Discussionmentioning
confidence: 94%
“…The particularly aggressive nature of SRCCs and its earlier onset in colorectal cancers has been highlighted in the literature [ 28 , 29 ]. These cancers have higher frequency of KRAS and BRAF mutations compared with conventional cancers [ 30 ], correlating to shorter overall survival [ 31 ].…”
Section: Discussionmentioning
confidence: 99%